Pharmaceutical services as shared responsibility in SUS: a logical framework proposal - Adriane Lopes Medeiros Simone; Nicolina Silvana Romano-Lieber; Oswaldo Yoshimi Tanaka (Instituto Nacional de Assistência Farmacêutica e Farmacoeconomia, 2022)
Objectives: To present a Logical Framework (LF) of Pharmaceutical Services (PS) in Unified Health System (SUS, Brazil). Methods: The LF results from the legislation synthesis and experts' consultation. Delphi methodology was used to create and quantify consensus between specialists. Results: Legislation selected (n= 183) were published mostly by Federal Level (88%), between 2010 and 2015 (91%). The legislation contained 304 sections that addressed inter-federal responsibilities, contemplating eight components of PS (selection, financing, programming and acquisition, logistics, use, management, education and research), and an array of 54 responsibilities and 73 products in charge of Federal, State and Municipal Governments, which support PS three main pillars: access to essential drugs, rational use of medicines and structuring of PS. Conclusions: PS is under shared responsibility by the three levels of government, thus, the successful implementation of this public policy depends on the joint effort. The LF allows a broader understanding of the role of SUS managers, can be useful to define strategies to implement PS in Health Care Networks, and above all provides a reference for the construction of theoretical evaluation models addressing PS as a shared responsibility in SUS.